Damage Detection & Evaluation in Glass Fibre Reinforced Polymer Laminated Composites - Singh, Gurdyal (My University, 2011)
Glass fibre-reinforced polymer (GFRP) laminated composites have been used as an alternative to other metals & alloys due to high strength-to-weight ratio, high stiffness-to-weight ratio, corrosion and fatigue resistance. These composites may be subjected to damages either due to manufacturing flaws like missing fibre, air-voids etc. or damages may develop under working condition due to environmental degradation or harsh loading conditions (delamination, cracks). Cost effective & reliable damage evaluation is quite critical for utilization of composite materials. In the area of non-destructive testing, ultrasonic wave propagation testing has proved to be very effective tool for damage detection & evaluation of health of subject. Ultrasonic testing uses transmission of high frequency stress waves into a material to detect imperfections or to locate changes in material properties. The most commonly used ultrasonic testing techniques include pulse echo and pulse transmission technique, where stress waves are introduced into subject structure and reflections (echoes) are returned to a receiver from internal imperfections. Pulse echo is used to locate the exact position of damage and pulse transmission is used to know the presence & magnitude of damage. Relative comparison of wave signatures in healthy and damaged composite laminates could lead to an indication related to the health of specimen being tested. This thesis presents results of evaluation of damages caused in GFRP laminated specimens subjected to hygro-thermal & mechanical loading. Also simulated delamination type defects of varying extent & location have been studied with help of ultrasonic guided waves in terms of their effects on corresponding signal. For hygro-thermal loading, two layers unidirectional glass fibre reinforced laminate specimens have been subjected to water & NaOH solution (5% by weight) at 45°C temperature for 15 & 30 days. Changes in strength of specimens has been evaluated & compared to ultrasonic signal. Similarly the specimens have been subjected to different levels of loading (25%, 50% & 75% of the ultimate tensile load) to inflict the damages due to loading in working conditions. Subsequently changes in ultrasonic test signatures for these specimens have been recorded & correlated to the ultrasonic signatures of unloaded specimens. Also simulated delamination defects of varying extent & location in different layers have been studied using ultrasonic testing.
ME, Mechanical Engineering
Keywords: Damage evaluation; Composite laminates; Guided ways